2010
DOI: 10.1016/j.chom.2009.12.007
|View full text |Cite
|
Sign up to set email alerts
|

A Type VI Secretion System of Pseudomonas aeruginosa Targets a Toxin to Bacteria

Abstract: The functional spectrum of a secretion system is defined by its substrates. Here we analyzed the secretomes of Pseudomonas aeruginosa mutants altered in regulation of the Hcp Secretion Island-I-encoded type VI secretion system (H1-T6SS). We identified three substrates of this system, proteins Tse1-3 (type six exported 1-3), which are coregulated with the secretory apparatus and secreted under tight posttranslational control. The Tse2 protein was found to be the toxin component of a toxin-immunity system and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
1,041
2
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 813 publications
(1,070 citation statements)
references
References 83 publications
22
1,041
2
5
Order By: Relevance
“…These multiple gene sets may act to repurpose the general type 6 secretory apparatus for delivery of effector proteins to different cell targets. While other T6SSs, such as that of P. aeruginosa and V. cholerae, have been found to have antibacterial properties, we were unable to observe this phenomenon in the S. enterica T6SS in solid LB agar-based competition assays against E. coli (data not shown) (22,33). In addition, a previous report found that deletion of the entire SCI genomic island resulted in a 50% reduction of HEp-2 epithelial cells but we were unable to observe an effect on the invasion of both HeLa and HEp-2 epithelial cells by our sciG and sciS mutants, suggesting that gut epithelial cells may not be the target of this system and that this reduction in invasion may be due to a different SCI-encoded factor (16).…”
Section: Figmentioning
confidence: 48%
See 1 more Smart Citation
“…These multiple gene sets may act to repurpose the general type 6 secretory apparatus for delivery of effector proteins to different cell targets. While other T6SSs, such as that of P. aeruginosa and V. cholerae, have been found to have antibacterial properties, we were unable to observe this phenomenon in the S. enterica T6SS in solid LB agar-based competition assays against E. coli (data not shown) (22,33). In addition, a previous report found that deletion of the entire SCI genomic island resulted in a 50% reduction of HEp-2 epithelial cells but we were unable to observe an effect on the invasion of both HeLa and HEp-2 epithelial cells by our sciG and sciS mutants, suggesting that gut epithelial cells may not be the target of this system and that this reduction in invasion may be due to a different SCI-encoded factor (16).…”
Section: Figmentioning
confidence: 48%
“…Many orthologs of genes within cluster 4 were identified, including the sciW and rhs1 genes; however, the extensive conservation of rhs-associated genes and their close similarity made drawing conclusions about these genes difficult. Evidence of conservation of gene pairs within each of these clusters is particularly interesting given the presence of toxin-antitoxin gene pairs found in other T6SS-encoding organisms (22).…”
Section: Figmentioning
confidence: 99%
“…Evolutionarily related Type VI secretion system (T6SS) is used by bacteria to deliver proteins into both bacterial and eukaryotic cells (Mougous et al , 2006; Pukatzki et al , 2006; Hood et al , 2010; MacIntyre et al , 2010; Durand et al , 2014; Ho et al , 2014; Alcoforado Diniz et al , 2015; Hachani et al , 2016). The current model of T6SS biogenesis and mode of action is largely based on well‐understood phage assembly (Leiman et al , 2009; Lossi et al , 2011, 2013; Ho et al , 2014; Zoued et al , 2014; Clemens et al , 2015; Kudryashev et al , 2015; Cianfanelli et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Based on our in vitro findings, we hypothesized that S. Typhimurium outcompetes K. oxytoca within the host gut in a T6SS-dependent manner. To test this notion, we used a mouse model to measure T6SS contactdependent activity (9). However, K. oxytoca does not represent a large portion of the gut microbiota (Fig.…”
Section: S Typhimurium T6ss Kills Microbiota Members and Is Enhanced Bymentioning
confidence: 99%
“…For example, some bacteria exert long-range inhibitory effects by secreting diffusible molecules such as antibiotics, bacteriocins, and H 2 O 2 (8). Interestingly, previous studies have shown that one molecular mechanism mediating such behavior is the widely conserved type VI secretion system (T6SS) (9). Many sequenced genomes of Gram-negative bacteria encode a T6SS, which could be present in more than one copy (10,11).…”
mentioning
confidence: 99%